Predictions of reinforced concrete durability in the marine environment - Mackechnie, James Ronald (Department of Civil Engineering, 2016)
This thesis presents an investigation where an empirical method is proposed for predicting the durability of reinforced concrete structures in the marine environment. The objective was to identify reliable means of characterizing early-age properties of concrete which affect durability and relate these to the durability performance of the material under marine conditions. Establishing a relationship between early-age testing and long-term performance of concrete is a necessary precursor to implementing a system of performance-based durability specifications.